Act local but don't think too global: The impact of ecological goal level on behavior. Issue 5 (2nd September 2016) - Moussaoui, Lisa S.; Desrichard, Olivier
ABSTRACT: Growing awareness of humanity's impact on the environment raises the question of how best to encourage pro-environmental actions. Numerous campaigns have been created to convince people to adopt environmentally friendly everyday behaviors, with varying success. The difficulty may be due, at least in part, to the huge gap between these small individual actions and the high-level goals, such as "saving the planet, " often used as incentives. We tested this hypothesis via four experiments. Studies 1 and 2 showed that high-level goals were less effective than low-level goals in promoting paper- and energy-saving behaviors. Study 3 showed that high-level goals engender lower perceived outcome expectancy and higher perception of cumulative effort. Study 4 showed that outcome expectancy mediates the direct effect of goal level on intention.